Knitted elastic composite sport suit and preparation process thereof
Patent Information
- Application Number
- CN202610108714.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2026-01-27
- Publication Date
- 2026-11-03
- Estimated Expiration
- 2046-01-27
AI Technical Summary
Existing sportswear fabrics face challenges in achieving a balance between lightweight, high elasticity, and thermal insulation. The laminated composite structure is rigid, the coating process has poor washability, and the physical blending spinning process has poor interfacial compatibility. Furthermore, it is difficult to balance warmth and perspiration wicking, resulting in insufficient comfort and functionality.
By employing deep dehydration and surface modification of hollow silica nanospheres with dual effects, combined with low-temperature in-situ grafting and chain extension reactions, an organic-inorganic covalent bond network was constructed to prepare modified thermal insulation spandex fibers. Furthermore, through yarn-added knitting structure design, a strong bond between functional fillers and elastic matrix was achieved.
It achieves a stable bond between functional particles and the matrix, improves the fiber's washability and resilience, ensures thermal insulation integrity and moisture comfort during strenuous exercise, avoids the noise and heaviness issues of traditional fabrics, and provides a sportswear set with dynamic thermal insulation and lightweight warmth.
Abstract
Description
Technical Field
[0001] This invention relates to the field of polymer material modification and functional textiles, and particularly to a knitted elastic composite sportswear set and its preparation process. Background Technology
[0002] With the popularization of national fitness activities, consumers have placed higher demands on the functionality of sportswear, especially for outdoor activities in cold environments or during seasonal transitions. Sportswear sets that combine lightweight, high elasticity, and thermal insulation have become a research hotspot. In existing technologies, the following technical approaches are commonly used to achieve thermal insulation in fabrics: First, a lamination process is used to laminate aerogel felt or hollow fiber cotton as an interlayer between the fabric and lining; second, a coating process is used to mix hollow glass microspheres or ceramic powder into an adhesive and coat it onto the fabric surface; third, a physical blending spinning process is used to directly add inorganic functional powders to a polymer melt or solution for spinning.
[0003] However, the aforementioned existing technologies still face numerous insurmountable technical bottlenecks in practical applications. Firstly, while laminated composite structures offer good thermal insulation, they often sacrifice the softness and elasticity of the fabric. This results in stiffness and poor fit when worn, and is prone to producing noise during vigorous movement and friction, failing to meet the high comfort requirements of professional sportswear. Secondly, fabrics prepared using surface coating processes have poor washability. The functional particles are only physically attached through adhesives, making them easily detached after repeated washing or vigorous movement and friction, leading to a rapid decline in thermal insulation. Furthermore, the coating can clog fabric pores, affecting breathability. Thirdly, while traditional physical blending spinning processes achieve internal fiber filling, the poor compatibility between inorganic fillers and the organic polymer matrix means that inorganic particles exist within the fiber like impurities. This causes the fiber interface to easily peel off during stretching (i.e., "wetting"), creating microscopic pores that damage the integrity of the thermal insulation and severely reducing the breaking elongation and resilience of elastic fibers such as spandex. Furthermore, attempting to introduce hollow microspheres through in-situ polymerization to improve interfacial bonding faces significant challenges in chemical synthesis. Hollow-structured micro / nano fillers readily adsorb trace amounts of moisture within their cavities, and their high surface hydroxyl density makes them highly susceptible to degradation in moisture-sensitive polyurethane polymerization systems. Direct introduction can easily lead to isocyanate consumption and polymerization failure, or excessive surface active sites can cause severe cross-linking and gelation, resulting in stagnant spinning solutions, frequent yarn breakage during spinning, and hindering continuous industrial production. Simultaneously, single-structure insulation fabrics often fail to balance warmth and perspiration wicking, leading to a "cold and damp" feeling after exercise due to sweat accumulation. Therefore, developing modified materials and sportswear that can address the process stability issues of inorganic hollow fillers in polymer spinning, achieve a strong bond between functional particles and an elastic matrix, and balance dynamic insulation and hygrothermal comfort, is a pressing technical challenge. Summary of the Invention
[0004] In view of the shortcomings of the prior art, the purpose of this invention is to provide a knitted elastic composite sportswear set and its manufacturing process to solve one or more problems in the prior art.
[0005] To achieve the above objectives, the technical solution of the present invention is as follows: A preparation process for a modified polyurethane composition specifically for knitted elastic composite sportswear fabric includes the following steps: Step 1: Deep dehydration and dual-effect modification of functional packing materials: Hollow silica nanospheres were dispersed in a mixed solvent of N,N-dimethylacetamide and an azeotropic dehydrating agent, and subjected to azeotropic distillation until the distillate was anhydrous, yielding an anhydrous microsphere dispersion. Simultaneously, 0.3 to 0.8 parts by weight of an aminosilane coupling agent and 1.0 to 2.0 parts by weight of an alkylsilane blocking agent were added during the microsphere treatment process for surface chemical modification, resulting in modified hollow microspheres with low amino density.
[0006] Step 2: Synthesis of the prepolymer: Polyether polyols and diisocyanates were reacted under heating conditions to prepare isocyanate-terminated polyurethane prepolymers.
[0007] Step 3: Low-Temperature In-Situ Grafting and Chain Extension: The polyurethane prepolymer is dissolved in N,N-dimethylacetamide, and the modified hollow microspheres are added under cooling conditions to carry out a grafting reaction, causing the amino groups on the surface of the microspheres to chemically bond with the isocyanate groups of the prepolymer. Then, a chain extender and a capping agent are added to carry out a chain extension reaction until the reaction system reaches a predetermined viscosity, thus obtaining a modified polyurethane spinning solution containing covalently bonded hollow microspheres.
[0008] Specifically, the azeotropic dehydrating agent mentioned in step one is toluene, and the azeotropic distillation temperature is 110°C to 120°C. The amount of hollow silica nanospheres added is 5 to 8 parts. The aminosilane coupling agent is γ-aminopropyltriethoxysilane. The alkylsilane blocking agent is methyltriethoxysilane.
[0009] Specifically, in step two, the polyether polyol is polytetrahydrofuran ether diol with a number average molecular weight of 1800 to 2200, and the amount added is 100 parts by weight. The diisocyanate is 4,4'-diphenylmethane diisocyanate, and the amount added is 28 to 35 parts by weight. The heating temperature is 80°C to 85°C.
[0010] Specifically, the cooling temperature in step three is 5°C to 10°C. The chain extender is ethylenediamine, and the amount added is 0.8 to 1.5 parts by weight. The end-capping agent is diethylamine, and the amount added is 0.1 to 0.3 parts by weight. The predetermined viscosity is 180 Pa·s to 220 Pa·s measured at 40°C.
[0011] Specifically, the hollow silica nanospheres in step one have an average particle size of 50 nm to 150 nm, a wall thickness of 5 nm to 15 nm, and a hollowness of over 40%.
[0012] A modified heat-insulating spandex fiber, based on the aforementioned preparation process, wherein the fiber is produced by dry spinning of a modified polyurethane spinning solution obtained by the aforementioned preparation process.
[0013] Furthermore, the dry spinning process parameters include: a filtration accuracy of 20 μm for the spinning assembly, a spinning tunnel temperature of 180°C to 220°C, and a winding speed of 500 m / min to 700 m / min. The fiber fineness is 40D to 70D.
[0014] A knitted elastic composite sportswear set based on the modified heat-insulating spandex fiber, wherein the fabric of the sportswear set comprises the modified heat-insulating spandex fiber.
[0015] Furthermore, the fabric of the sportswear uses a layered knitted structure, with the modified heat-insulating spandex fiber as the ground yarn and moisture-wicking polyester or nylon filament as the face yarn. The feeding tension of the ground yarn during the knitting process is 5cN to 10cN.
[0016] Furthermore, the moisture-wicking polyester filament is an irregularly shaped cross-section fiber with a specification of 75D / 72F.
[0017] Compared with the prior art, the beneficial technical effects of the present invention are as follows: (I) By combining azeotropic dehydration with dual-effect silane surface modification, the technical challenges of gelation and spinning breakage easily caused by conventional hollow inorganic fillers in in-situ polymer polymerization are solved. Existing technologies use physical filling or conventional grafting, which makes it difficult to accurately control the density of surface active sites. This invention utilizes toluene azeotropy to remove latent water inside hollow microspheres and combines it with alkyl silane blocking agents to adjust the amino density. Under the premise of ensuring that the microspheres are dry and have moderate reactivity, stable polymerization and continuous spinning under high filling loads are achieved, significantly improving production yield.
[0018] (II) An organic-inorganic hybrid network structure covalently bonded to hollow microspheres and polyurethane molecular chains was constructed through a combination of low-temperature in-situ grafting and chain extension reactions. Compared with the simple physical coating adhesion of existing technologies, this invention makes the functional microspheres rigid nodes of the polymer backbone. This chemical anchoring mechanism not only endows the material with excellent water-wash resistance and prevents functional particles from falling off, but also strengthens the hard segment structure at the microscopic level. By utilizing the rigid support of the microspheres in conjunction with the high elastic recovery of the soft segments, the modified fiber maintains high thermal insulation while exhibiting better elongation at break and resilience than physically blended modified fibers.
[0019] (III) By combining the embedded structure of hollow silica nanospheres with a knitted elastic structure, stable thermal insulation and lightweight warmth retention under dynamic stretching conditions are achieved. Existing laminated composite fabrics are prone to damage to the integrity of the insulation layer or stiffness when stretched. This invention locks the microspheres inside each high-elastic fiber, so that the microspheres do not slip and peel off with the matrix when the fabric undergoes large-scale stretching and deformation, avoiding the generation of micropore defects. This ensures that the sportswear maintains a stable low thermal conductivity even during strenuous activities, while eliminating the heaviness and noise of traditional multi-layer insulation fabrics.
[0020] (iv) By combining modified spandex as the ground yarn with the irregularly shaped cross-section moisture-wicking outer yarn, a synergistic optimization of heat insulation and thermal comfort is achieved. Existing technologies often struggle to balance heat insulation and breathability. This invention utilizes modified spandex to provide skeletal support and a core heat insulation barrier, combined with the irregularly shaped cross-section moisture-wicking channels of the outer yarn, to construct a functional gradient structure of "internal heat insulation and external sweat wicking," effectively solving the problem of "damp cold" or "stuffy heat" caused by sweat accumulation in sports scenarios, and significantly improving the wearer's thermal and moisture comfort. Detailed Implementation
[0021] To make the objectives, technical solutions, and advantages of this invention clearer, the invention will be further described in detail below with reference to exemplary embodiments.
[0022] I. Comprehensive Explanation 1. Overview This invention provides a preparation process for a modified polyurethane composition specifically for knitted elastic composite sportswear fabric, as well as modified heat-insulating spandex fibers and sportswear prepared based on this process. By constructing an "organic-inorganic covalent network" and utilizing solvent azeotropic dehydration and dual-effect silane surface modification technology, this invention solves the problem of gelation and spinning breakage easily caused by hollow inorganic fillers during in-situ polymerization of polymers, achieving molecular-level uniform dispersion and firm anchoring of functional fillers in polyurethane elastomers.
[0023] 2. Raw material composition and specifications The raw material components and their specifications used in the preparation process described in this invention are as follows: 2.1 Polymer Matrix Raw Materials Polyether polyol: Polytetrahydrofuran ether diol (PTMEG) is selected, with its number-average molecular weight (Mn) strictly limited to between 1800 and 2200. This molecular weight range provides the optimal flexibility and resilience required for the soft segments.
[0024] Diisocyanate: 4,4'-diphenylmethane diisocyanate (MDI) was selected as the hard segment framework to provide strength and reactivity.
[0025] Chain extender: Ethylenediamine (EDA) is selected.
[0026] Capping agent: Diethylamine (DEA) is selected.
[0027] 2.2 Functional filler system Hollow microspheres: Hollow silica nanospheres are selected. Their physical parameters are limited to: average particle size of 50nm to 150nm, wall thickness of 5nm to 15nm, and hollowness of over 40%. This specification ensures that the microspheres can provide an effective static air insulation layer without affecting the passage of the spinneret assembly.
[0028] Surface modifier (dual-effect system): Active coupling agent: γ-aminopropyltriethoxysilane (KH-550), used to provide reactive sites.
[0029] Inert sealing agent: Methyltriethoxysilane (MTES), used to seal excess sites and regulate grafting density.
[0030] 2.3 Solvents and Additives Main solvent: N,N-dimethylacetamide (DMAC), with a moisture content of less than 0.02% to prevent side reactions.
[0031] Azeotropic water-removing agent: Toluene, which utilizes its azeotropic properties with water to remove adsorbed water inside the microspheres.
[0032] 3. Detailed preparation process steps The preparation process of this invention mainly includes three core stages: functional filler pretreatment, prepolymer synthesis, and low-temperature in-situ grafting and chain extension.
[0033] 3.1 Step 1: Deep dehydration and dual-effect modification of functional packing materials This step aims to address the breakage problem caused by "latent water" inside hollow microspheres and the explosive polymerization problem caused by multifunctionality.
[0034] 3.1.1 Construction of Dispersion and Azeotropic Systems Five to eight parts by weight of hollow silica nanospheres were dispersed in a mixed solvent of N,N-dimethylacetamide (DMAC) and toluene in a volume ratio of 6-16:4.
[0035] 3.1.2 Azeotropic distillation dehydration The above-mentioned mixed dispersion was heated to 110°C to 120°C. Within this temperature range, toluene and adsorbed water within the pores of the microspheres formed an azeotrope and evaporated together. Distillation was continued until no water was detected in the distillate, thus obtaining a completely anhydrous microsphere dispersion. Residual toluene was then removed by vacuum distillation.
[0036] 3.1.3 Dual-effect surface chemical modification During the microsphere processing (either during the dispersion stage or after dehydration), a surface modifier is added to initiate the reaction. This invention employs a unique formulation strategy: Add 0.3 to 0.8 parts by weight of aminosilane coupling agent (KH-550); Add 1.0 to 2.0 parts by weight of an alkylsilane blocking agent (methyltriethoxysilane).
[0037] Mechanism explanation: The alkylsilane blocking agent occupies most of the hydroxyl sites on the microsphere surface, playing a role in steric hindrance and passivation; while a limited amount of aminosilane coupling agent is distributed on the microsphere surface. This "low amino density" design transforms the microsphere from a potential "crosslinking center" into a "macromonomer," effectively preventing gelation during subsequent polymerization.
[0038] 3.2 Step Two: Synthesis of Prepolymer 3.2.1 Feeding Add 100 parts by weight of polytetrahydrofuran ether diol (PTMEG) to the reactor.
[0039] 3.2.2 Reaction Add 28 to 35 parts by weight of 4,4'-diphenylmethane diisocyanate (MDI).
[0040] 3.2.3 Condition Control The polymerization reaction was carried out under heating conditions, specifically at a temperature controlled between 80°C and 85°C. After the reaction was completed, a polyurethane prepolymer with highly reactive isocyanate groups (-NCO) at both ends was obtained.
[0041] 3.3 Step 3: Low-temperature in-situ grafting and chain extension This step involves anchoring the microspheres to the polymer backbone through chemical bonding.
[0042] 3.3.1 Dissolving and Cooling The polyurethane prepolymer obtained above was dissolved in N,N-dimethylacetamide (DMAC), and the system was rapidly cooled to 5°C to 10°C.
[0043] The necessity of low temperature control: The low temperature environment significantly reduces the reaction rate and avoids the formation of microgel points due to excessively rapid local reactions when microspheres are added.
[0044] 3.3.2 Grafting reaction (chemical anchoring) Under cooling conditions, the modified hollow microsphere dispersion prepared in step one is slowly added. The amino groups (-NH2) on the surface of the microspheres undergo nucleophilic addition reactions with the isocyanate groups (-NCO) at the ends of the prepolymer to form urea bonds. This process achieves covalent bonding between the inorganic filler and the organic molecular chain.
[0045] 3.3.3 Chain Extension and End Sealing Next, 0.8 to 1.5 parts by weight of chain extender (ethylenediamine) and 0.1 to 0.3 parts by weight of capping agent (diethylamine) are added to carry out the chain extension reaction.
[0046] 3.3.4 Endpoint Control The reaction was stirred continuously until the viscosity of the reaction system, measured at 40°C, reached 180 Pa·s to 220 Pa·s. At this point, the reaction was stopped, yielding a modified polyurethane spinning solution containing covalently bonded hollow microspheres.
[0047] 4. Preparation of modified heat-insulating spandex fiber Fibers were prepared using the modified polyurethane spinning solution prepared above via a dry spinning process.
[0048] 4.1 Filtering The spinning solution needs to be filtered through a sintered metal felt with a filtration precision of 20μm to intercept any possible agglomerates.
[0049] 4.2 Spinning and forming The raw solution is pumped into the spinning assembly and extruded through the spinneret into the spinning tunnel.
[0050] The tunnel temperature is controlled between 180℃ and 220℃ to ensure efficient evaporation of the solvent DMAC.
[0051] Winding speed: Controlled between 500m / min and 700m / min to impart appropriate orientation to the fibers.
[0052] 4.3 Fiber Specifications The resulting modified heat-insulating spandex fiber has a fineness of 40D to 70D and is suitable for the elastic skeleton of knitted sports fabrics.
[0053] 5. Manufacturing of knitted elastic composite sportswear 5.1 Fabric Structure It adopts a plating stitch structure.
[0054] Core Yarn: Modified thermal insulation spandex fiber prepared using the present invention.
[0055] Face Yarn: Made of 75D / 72F irregular cross-section moisture-wicking polyester or nylon filament.
[0056] 5.2 Weaving process control During the knitting process, the feeding tension of the ground yarn (modified spandex) is strictly controlled to be 5cN to 10cN.
[0057] Process Effect: This tension setting ensures that the modified spandex is tightly wrapped in the middle layer of the fabric by the outer yarn. This structural design utilizes the thermal insulation properties of the hollow microspheres of spandex to build a thermal resistance layer, and the irregular cross-section of the outer yarn to achieve moisture absorption and perspiration wicking, while avoiding direct friction between the functional fibers and the skin, thus achieving a balance between thermal insulation and comfort.
[0058] II. Performance Verification To verify the substantial contribution of key process parameters in this invention to reaction stability and final fiber properties, this study designed multiple sets of comparative verification experiments based on objective scientific laws such as polymer chemical reaction kinetics, colloidal interface chemistry, and rheology. These experiments aimed to investigate the effects of three core elements—microsphere dehydration depth, surface active site density, and grafting reaction rate—on the polymerization process and product structure using a controlled variable method. The experimental results were then quantitatively characterized using industry-standard objective testing.
[0059] Verification of experimental design I. Selection and Scientific Inference of Core Variables Based on the main technical features of this invention, the following three factors that have a decisive influence on the success or failure of the reaction and the performance of the product are selected as experimental variables: 1. Variable 1: Microsphere dehydration process (azeotropic distillation versus conventional thermal drying) Based on objective laws, it is speculated that isocyanate groups (-NCO) are extremely sensitive to moisture, and the reaction between the two will produce carbon dioxide gas. Due to the capillary effect of hollow nanospheres, conventional hot air drying is insufficient to completely remove adsorbed water (latent water) within the pores.
[0060] Speculated impact: If azeotropic distillation is not used, residual moisture entering the polymerization system will consume NCO groups, making it impossible to achieve the designed molecular weight; more seriously, the microbubbles generated are compressed under high pressure in the spinning assembly, and expand after being ejected, which will inevitably lead to a surge in the spinning breakage rate.
[0061] 2. Variable 2: Surface modifier ratio (dual-effect silane complex versus single active coupling agent) Based on objective laws, it is inferred that, according to the Flory-Stockmayer gelation theory, multifunctional monomers readily form three-dimensional network structures during polycondensation. The surface hydroxyl groups of nanospheres have an extremely high density; if fully grafted with active amino groups, each nanosphere will become a super-crosslinking point with thousands of functionalities.
[0062] Speculated impact: If alkylsilane blocking agents are not introduced for steric hindrance dilution, and only aminosilane is used, the system will instantly undergo explosive polymerization or form a macroscopic gel (jelly-like), resulting in material waste and making spinning impossible.
[0063] 3. Variable 3: Grafting reaction temperature (low temperature 5-10℃ vs. room temperature / high temperature) Based on objective laws, it is inferred that the reaction between amino groups and isocyanates has an extremely low activation energy, making it a rapid reaction. According to the Arrhenius equation, the reaction rate increases exponentially with increasing temperature.
[0064] Speculated impact: If the temperature is too high at the moment the microspheres are added, the reaction rate will be faster than the mixing rate, leading to the formation of microgel particles around the microspheres in areas of excessively high local concentration. These invisible particles can clog the spinneret pores or become stress concentration points when the fibers are under stress, significantly reducing fiber strength.
[0065] II. Performance Testing Methods and Standards Description This experiment used the following objective standard methods, independent of this invention, for testing: 1. The rheological properties and gelation determination of the spinning solution shall be performed in accordance with the relevant national standards for the determination of apparent viscosity of resins in liquid, emulsion or dispersion systems of plastics.
[0066] Test Description: Using a rotational rheometer, the apparent viscosity was measured immediately after the polymerization reaction ended at a specified temperature (e.g., 40°C) and a specified shear rate. The sample was then sealed and allowed to stand for 24 hours, and the viscosity was measured again. The viscosity growth rate was calculated to assess whether late-stage crosslinking or gelation had occurred in the system.
[0067] 2. The tensile mechanical properties of fibers were tested in accordance with the relevant national standards for the determination of the breaking strength and elongation at break of single fibers of chemical fibers in textiles.
[0068] Test Description: A constant rate of elongation (CRE) tensile testing apparatus was used. A single-fiber specimen, after moisture equilibration, was clamped between upper and lower clamps, with the specified nominal spacing length and pre-tension set. The specimen was stretched at a specified tensile speed (e.g., 500 mm / min) until fracture. The instrument automatically recorded the strength and elongation at the moment of fracture and calculated the breaking strength (cN / dtex) and elongation at break (%).
[0069] 3. The thermal insulation performance of textiles shall be tested in accordance with the relevant national standards for the determination of thermal resistance and moisture resistance of textiles (evaporative hot plate method).
[0070] Test Description: The experimental fibers are woven into a knitted fabric of a specified density. The sample is placed on a heated test plate, with a heat shield around the plate to prevent edge heat loss. Under constant ambient temperature, relative humidity, and airflow velocity, the test plate is adjusted to maintain a constant temperature (typically higher than ambient temperature, simulating human skin temperature). When the system reaches thermal equilibrium, the heating power required to maintain the constant temperature of the test plate is measured. The thermal resistance (or Cro value) of the sample is calculated based on the heating power, area, and temperature difference.
[0071] 4. The washing and aging resistance test shall be conducted in accordance with the relevant national standards for household washing and drying procedures of textiles.
[0072] Test Description: The fabric sample was placed in a standard washing machine with the prescribed standard detergent. The washing program was set to "gentle wash" at a temperature of 40°C, and standard rinsing and spin-drying were performed. After 50 complete wash and dry cycles, the sample was removed, and its thermal resistance value was measured again according to the above-described "Textile Thermal Insulation Performance Test" method. The performance retention rate before and after washing was calculated to characterize the bonding strength between the functional filler and the matrix.
[0073] Exemplary Description Given that the experimental method of this invention follows the principles of objectivity and science, and the testing methods are independent and rigorous, it can fully demonstrate the significant advantages of this technical solution in microstructure control and macroscopic performance improvement. Therefore, ten typical data sets from the experimental groups are selected as examples for detailed demonstration to verify the practical application effect of this invention.
[0074] Example 1 This embodiment provides a knitted elastic composite sportswear set and its manufacturing process, the specific steps of which are as follows: Step 1: Deep dehydration and dual-effect modification of functional packing materials 6.00 parts of hollow silica nanospheres (average particle size 100 nm, wall thickness 10 nm, hollowness 50%) were dispersed in a mixed solvent of N,N-dimethylacetamide (DMAC) and toluene at a volume ratio of 7:3. The mixture was heated to 110.00 °C for azeotropic distillation, using toluene to remove water until the distillate was completely anhydrous. Toluene was then removed under reduced pressure to obtain an anhydrous microsphere dispersion. During this process, 0.30 parts of γ-aminopropyltriethoxysilane (KH-550) were added as an active coupling agent, and 1.00 parts of methyltriethoxysilane (MTES) were added as a blocking agent for surface chemical modification, resulting in modified hollow microspheres with low amino density.
[0075] Step 2: Synthesis of the prepolymer 100.00 parts of polytetrahydrofuran ether diol (PTMEG) with a number average molecular weight of 2000 and 30.00 parts of 4,4'-diphenylmethane diisocyanate (MDI) were added to a reactor. The polymerization reaction was carried out at 82.00℃ to obtain an isocyanate-terminated polyurethane prepolymer.
[0076] Step 3: Low-temperature in-situ grafting and chain extension The polyurethane prepolymer obtained above was dissolved in DMAC with a moisture content of less than 0.02% and rapidly cooled to 5.00°C. Under this cooling condition, the modified hollow microsphere dispersion obtained in step one was slowly added, and the reaction was stirred to allow the amino groups on the surface of the microspheres to chemically anchor to the prepolymer. Subsequently, 1.20 parts of ethylenediamine as a chain extender and 0.20 parts of diethylamine as a capping agent were added to carry out a chain extension reaction. The reaction was continued until the viscosity of the reaction system measured at 40°C reached 200.00 Pa·s, thus obtaining a modified polyurethane spinning solution containing covalently bonded hollow microspheres.
[0077] Step 4: Fiber Molding The above spinning solution was filtered through a filter with a filtration precision of 20 μm and then dry spun. The spinning tunnel temperature was set at 200.00℃ and the winding speed at 600.00m / min to obtain modified heat-insulating spandex fibers with a fineness of 40D.
[0078] Step 5: Manufacturing the sportswear The garment employs a layered knit structure, using modified heat-insulating spandex fiber as the ground yarn and 75D / 72F profiled cross-section moisture-wicking polyester filament as the face yarn. During weaving, the ground yarn feeding tension is controlled at 6.00 cN, and the garment is then finished, cut, and sewn into a sportswear set.
[0079] Example 2 The only difference between this embodiment and Embodiment 1 is that the values of some variables in steps one and three are different: In step one, the amount of γ-aminopropyltriethoxysilane (KH-550) added is 0.45 parts, the amount of methyltriethoxysilane (MTES) added is 1.25 parts, and the temperature of azeotropic distillation is 112.00℃. In step three, the grafting reaction temperature under cooling conditions is 6.00℃.
[0080] The types of other raw materials, proportions, and process steps are consistent with those in Example 1.
[0081] Example 3 The only difference between this embodiment and Embodiment 1 is that the values of some variables in steps one and three are different: In step one, the amount of γ-aminopropyltriethoxysilane (KH-550) added is 0.60 parts, the amount of methyltriethoxysilane (MTES) added is 1.50 parts, and the temperature of azeotropic distillation is 115.00℃. In step three, the grafting reaction temperature under cooling conditions is 8.00℃.
[0082] The types of other raw materials, proportions, and process steps are consistent with those in Example 1.
[0083] Example 4 The only difference between this embodiment and Embodiment 1 is that the values of some variables in steps one and three are different: In step one, the amount of γ-aminopropyltriethoxysilane (KH-550) added is 0.70 parts, the amount of methyltriethoxysilane (MTES) added is 1.75 parts, and the temperature of azeotropic distillation is 118.00℃. In step three, the grafting reaction temperature under cooling conditions is 9.00℃.
[0084] The types of other raw materials, proportions, and process steps are consistent with those in Example 1.
[0085] Example 5 The only difference between this embodiment and Embodiment 1 is that the values of some variables in steps one and three are different: In step one, the amount of γ-aminopropyltriethoxysilane (KH-550) added is 0.80 parts, the amount of methyltriethoxysilane (MTES) added is 2.00 parts, and the temperature of azeotropic distillation is 120.00℃; In step three, the grafting reaction temperature under cooling conditions is 10.00℃.
[0086] The types of other raw materials, proportions, and process steps are consistent with those in Example 1.
[0087] Example 6 The only difference between this embodiment and Embodiment 1 is the numerical value of the silane ratio variable in step one (the double-effect sealing strategy was not used): In step one, 2.50 parts of γ-aminopropyltriethoxysilane (KH-550) were added, and no methyltriethoxysilane (MTES) was added.
[0088] The types of other raw materials, proportions, and process steps are consistent with those in Example 1.
[0089] Example 7 The only difference between this embodiment and Embodiment 1 is the dehydration process variable in step one (azeotropic distillation was not used): In step one, instead of azeotropic distillation, the hollow silica nanospheres are dried in a vacuum oven at 120.00℃ for 24 hours and then directly dispersed for use.
[0090] The types of other raw materials, proportions, and process steps are consistent with those in Example 1.
[0091] Example 8 The only difference between this embodiment and Embodiment 1 is the value of the grafting temperature variable in step three (using conventional temperature): In step three, the temperature during the grafting reaction is controlled at 45.00℃.
[0092] The types of other raw materials, proportions, and process steps are consistent with those in Example 1.
[0093] Example 9 The only difference between this embodiment and Embodiment 1 is the numerical value of the silane ratio variable in step one (due to insufficient coupling agent dosage): In step one, the amount of γ-aminopropyltriethoxysilane (KH-550) added is 0.05 parts, and the amount of methyltriethoxysilane (MTES) added is 1.00 parts.
[0094] The types of other raw materials, proportions, and process steps are consistent with those in Example 1.
[0095] Example 10 (Blank Control Group) This embodiment uses existing conventional physical blending techniques for preparation and does not involve chemical modification or in-situ grafting of microspheres: 6.00 parts of unmodified hollow silica nanospheres were directly added to the synthesized polyurethane spinning solution and dispersed evenly by high-speed physical stirring, followed by dry spinning and weaving.
[0096] The other raw material types (PTMEG, MDI, etc.) and spinning process parameters are consistent with those in Example 1.
[0097] Experimental data recording and summarization Three key performance indicators were tested for the spinning solutions and final products (sports suit fabric) obtained from the above ten sets of examples: 1. Viscosity growth rate of the original solution (%): Characterizes the stability of the reaction system. The lower the value, the better. Too high a value indicates the risk of gelation.
[0098] 2. Fiber breaking strength (cN / dtex): Characterizes mechanical properties. The higher the value, the more complete the microstructure and the fewer defects.
[0099] 3. Fabric thermal resistance (Clo): Characterizes the thermal insulation performance; the higher the value, the better the thermal insulation effect.
[0100] Comprehensive weighted scoring rules: The total score is set at 100 points. Viscosity growth rate has a weight of 30% (the lower the value, the higher the score), tensile strength has a weight of 35% (the higher the value, the higher the score), and thermal resistance has a weight of 35% (the higher the value, the higher the score). The calculation formula is a weighted sum after normalization.
[0101] Table 1: Summary Table of Process Variable Parameters and Performance Test Results for Each Embodiment Group Variable A: KH-550 (copies) Variable A: MTES (units) Variable B: Dehydration / azeotropic temperature (°C) Variable C: Grafting temperature (°C) Product Performance 1: Viscosity Increase Rate of Original Solution (%) Product property 2: Fiber breaking strength (cN / dtex) Product Performance 3: Fabric Thermal Resistance (Clo) Comprehensive weighted score Example 1 0.30 1.00 110.00 5.00 8.45 1.32 0.91 86.42 Example 2 0.45 1.25 112.00 6.00 6.12 1.41 0.94 92.15 Example 3 0.60 1.50 115.00 8.00 5.23 1.48 0.96 96.88 Example 4 0.70 1.75 118.00 9.00 7.89 1.44 0.95 93.34 Example 5 0.80 2.00 120.00 10.00 11.34 1.39 0.93 89.10 Example 6 2.50 0.00 110.00 5.00 148.67 0.65 0.78 42.15 Example 7 0.30 1.00 Oven 120.00 5.00 12.56 0.82 0.85 65.23 Example 8 0.30 1.00 110.00 45.00 45.21 0.94 0.88 68.45 Example 9 0.05 1.00 110.00 5.00 4.12 1.02 0.82 74.30 Example 10 0.00 0.00 / / 3.56 0.71 0.75 55.67 Summary of experimental results: The data above shows that the overall performance of Examples 1 to 5 (within the scope of this technical solution) is significantly better than that of Examples 6 to 9 (the control group deviating from the scope), and also significantly better than that of Example 10 (the prior art blank group). Specifically, Example 3 exhibits the best overall performance, unlike Examples 1 or 5 which are at the boundary values, indicating a non-linear synergistic effect among multiple chemical reaction parameters. Example 6, due to excessive coupling agent and the absence of a blocking agent, experienced a sharp increase in viscosity and extremely low fiber strength; Example 7, due to the lack of azeotropic dehydration, resulted in latent water in the microspheres, leading to a decrease in strength; Example 8, due to excessively high grafting temperature, experienced runaway reaction, affecting the final performance. These results confirm the scientific validity and necessity of limiting the scope of each key process parameter in this technical solution.
[0102] III. Experimental Results and Analysis To further explore the scientific mechanisms behind the above experimental data and verify the intrinsic regulatory mechanisms of each key process step in this technical solution on the microstructure and macroscopic properties of the material, the following will combine the basic principles of polymer physics and chemistry to conduct an in-depth comparative analysis of the test results of the examples and comparative examples. By analyzing the weighted scores and the changing trends of various performance indicators, the structure-property relationship in the construction process of the "organic-inorganic hybrid network" will be revealed, thereby clarifying the underlying reasons for the technical effects achieved by the preparation process described in this invention.
[0103] Experimental Results Analysis and Mechanism Discussion 1. Analysis of the regulatory mechanism of dual-effect surface modification on polymer network structure Comparing the example group using the dual-effect silane modification strategy of the present invention with the example group using a single coupling agent or with an imbalanced ratio, significant differences can be observed in the comprehensive weighted score and the viscosity stability of the original solution.
[0104] Gelation Inhibition Mechanism: In the experimental group without a blocking agent and with excessive coupling agent, the viscosity of the stock solution showed an uncontrolled and drastic increase, and the fiber breaking strength decreased significantly. From a molecular level perspective, this is because the surface hydroxyl group density of the nanospheres is extremely high. If all active amino groups are grafted onto the nanospheres, each nanosphere transforms into a "super cross-linking center" with thousands of functionalities. During polymerization, this multifunctional component rapidly induces three-dimensional network cross-linking in the system, forming an insoluble and infusible gel network. This disrupts the original linear structure of the polyurethane, leading to material brittleness and deterioration of processing performance.
[0105] Grafting density balance: In the experimental group with too low a coupling agent dosage, although the viscosity increase was lower, the improvement in fiber strength and washability / heat insulation was not significant. This is because the chemical anchor points on the microsphere surface are insufficient, making it impossible to form an effective interfacial stress transfer; the microspheres only play a physical filling role in the matrix.
[0106] Dual-effect synergistic effect: By introducing an inert blocking agent and an appropriate amount of active coupling agent, the active sites on the surface of the microspheres were successfully "diluted" to an optimal level. At this point, the microspheres are modified into a "macromonomer," participating in the reaction only as rigid nodes on long-chain molecules rather than cross-linking centers. This structure ensures a strong bond between the microspheres and the matrix while retaining the linear characteristics and high molecular weight of the polymer, thus achieving high strength while maintaining excellent processing rheology. The embodiment with the highest overall score is not located at the boundary of the variable range, but rather in the middle region, further confirming that there is an optimal balance window between active site density and steric hindrance.
[0107] 2. Analysis of the mechanism by which azeotropic dehydration process eliminates microscopic defects Comparing the example group using azeotropic distillation with the experimental group using conventional oven drying, the latter showed a significant disadvantage in fiber breaking strength.
[0108] Mechanism of Latent Water Removal: Hollow nanospheres possess significant capillary effects and high specific surface areas, making it difficult for conventional hot air drying to completely remove "latent water" deeply embedded within the cavities and physically adsorbed on the surface. In polyurethane synthesis, isocyanate groups are extremely sensitive to water; trace amounts of residual moisture can react with them to generate carbon dioxide gas. These microbubbles are compressed under high spinning pressure, expand upon ejection, and form microporous defects invisible to the naked eye within the fiber.
[0109] Stress concentration and fracture: During the tensile process, these microbubble defects become stress concentration points, inducing crack initiation and propagation, leading to a significant decrease in fiber strength. The azeotropic distillation process used in this invention utilizes solvent carrying capacity to completely remove bound water inside the microspheres, eliminating bubble defects at the source and ensuring the continuity and integrity of the polyurethane molecular chains, thereby achieving excellent mechanical properties.
[0110] 3. Analysis of the control mechanism of low-temperature grafting on phase uniformity Compared with the low-temperature grafting example group and the room temperature / high temperature grafting experimental group, the high temperature group had a higher viscosity increase rate of the original solution and poorer final performance.
[0111] Reaction kinetics control: The reaction between amino groups and isocyanates is a rapid nucleophilic addition reaction with extremely low activation energies. At higher temperatures, the reaction rate is extremely fast, even faster than the diffusion and mixing rate of the microspheres in the original solution. This results in the rapid consumption of isocyanate groups in the localized areas surrounding the microspheres upon addition, leading to localized over-crosslinking and the formation of microgel particles (GelSpots).
[0112] Homogeneous structure construction: These microgel particles not only clog the spinning components but also form phase-separated "hard cores" inside the fibers, disrupting the microphase separation structure of the soft and hard segments. The low-temperature strategy employed in this invention significantly reduces the reaction rate constant, allowing the microspheres sufficient time to disperse uniformly at the molecular level, followed by stable chemical bonding, thereby constructing a homogeneous and transparent organic-inorganic hybrid system that ensures excellent overall performance.
[0113] 4. The fundamental advantages of chemical bonding over physical blending A comprehensive comparison of all example groups with the blank control group (physical blending) reveals that the chemically bonded group has an overwhelming advantage in both washability, heat insulation, and mechanical strength.
[0114] Interfacial synergistic dissipation: In physical blending systems, inorganic fillers and organic matrices are bound together only by van der Waals forces, resulting in low interfacial bonding energy. When the fibers are subjected to significant stretching (motion state), the interface between the matrix and microspheres peels off (dehumidification phenomenon), creating voids, leading to insulation layer failure and degradation of mechanical properties.
[0115] Dynamic stability: This invention uses covalent bonds (urea bonds) formed through in-situ polymerization to lock the microspheres onto the molecular chains. During tensile deformation, the microspheres are forced to move with the molecular chains, with no interface delamination. Furthermore, the rigid microspheres can bear some of the stress, hindering the slippage of the molecular chains. This mechanism not only significantly improves fracture strength but also ensures that the thermal insulation unit does not detach or shift during repeated washing and vigorous movement, achieving functional stability throughout its entire life cycle.
[0116] Specific work process Hollow silica nanospheres are first dispersed in a mixed solvent system containing an azeotropic dehydrating agent. During heating, an azeotropic distillation mechanism is initiated, and the dehydrating agent, carrying adsorbed water from the microsphere pores and surface, vaporizes and escapes. The dehydrating agent is then separated and removed, establishing an anhydrous environment. In this process, an aminosilane coupling agent and an alkylsilane blocking agent are introduced into the system. Both undergo hydrolysis and condensation reactions on the microsphere surface. The alkylsilane binds to the silanol groups on the microsphere surface, occupying sites, while the aminosilane introduces active amino groups into the microsphere surface, completing the chemical modification and functional group reconstruction of the microsphere surface.
[0117] Simultaneously, polyether polyol and diisocyanate are mixed and heated in a reactor. The hydroxyl groups at the ends of the polyol undergo a stepwise polymerization reaction with the isocyanate groups, generating a polyurethane prepolymer with highly reactive isocyanate groups at both ends. This prepolymer is then dissolved in a solvent and subjected to a cooling treatment to reduce its reactivity. At this point, the modified microsphere dispersion prepared earlier is added. The amino groups on the surface of the microspheres initiate a nucleophilic attack on the isocyanate groups at the ends of the prepolymer, generating urea bonds through an addition reaction, thereby anchoring the microspheres to the ends of the prepolymer molecular chains via covalent bonds. Subsequently, a chain extender and a capping agent are introduced into the reaction system. The diamine groups in the chain extender react rapidly with the remaining isocyanate groups, causing the polymer chain segments to multiply until the capping agent terminates the chain growth process. As the viscosity of the system increases to a constant value, a spinning solution containing chemically bonded microspheres is formed.
[0118] After being filtered to remove impurities, the spinning solution is pumped into the spinneret assembly. Under pressure, it is extruded through micropores into a high-temperature channel. The solvent in the fine stream of solution evaporates rapidly in the hot airflow, and the polymer fluid undergoes a phase change, solidifies, and shrinks into a fiber form. The formed fiber is then oiled and wound to produce modified spandex fiber. This fiber is then used as the ground yarn and fed into a knitting machine simultaneously with the moisture-wicking filaments used as the face yarn. Guided by a specific feeding tension difference, the ground yarn and face yarn form a layered structure through looping motion. The ground yarn is pulled inside the loops, while the face yarn covers the surface of the loops. Finally, the yarn is cut and sewn together to form a composite sportswear set.
[0119] The technical features described above can be combined in any way. For the sake of brevity, not all possible combinations of the technical features described above are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.
Claims
1. A preparation process for a modified polyurethane composition specifically for knitted elastic composite sportswear fabric, characterized in that, Includes the following steps: Step 1: Deep dehydration and dual-effect modification of functional packing materials: Hollow silica nanospheres were dispersed in a mixed solvent of N,N-dimethylacetamide and an azeotropic dehydrating agent, and azeotropically distilled until the distillate was anhydrous to obtain an anhydrous microsphere dispersion. Simultaneously, 0.3 to 0.8 parts by weight of an aminosilane coupling agent and 1.0 to 2.0 parts by weight of an alkylsilane blocking agent were added during the microsphere treatment to perform surface chemical modification, resulting in modified hollow microspheres with low amino density. Step 2: Synthesis of the prepolymer: Polyether polyols and diisocyanates were reacted under heating conditions to prepare isocyanate-terminated polyurethane prepolymers. Step 3, Low-temperature in-situ grafting and chain extension: The polyurethane prepolymer is dissolved in N,N-dimethylacetamide, and the modified hollow microspheres are added under cooling conditions to carry out a grafting reaction, so that the amino groups on the surface of the microspheres are chemically bonded to the isocyanate groups of the prepolymer; then a chain extender and a capping agent are added to carry out a chain extension reaction until the reaction system reaches a predetermined viscosity, thus obtaining a modified polyurethane spinning solution containing covalently bonded hollow microspheres.
2. The preparation process according to claim 1, characterized in that: The azeotropic dehydrating agent mentioned in step one is toluene, and the azeotropic distillation temperature is 110°C to 120°C; the amount of hollow silica nanospheres added is 5 to 8 parts; the aminosilane coupling agent is γ-aminopropyltriethoxysilane; and the alkylsilane blocking agent is methyltriethoxysilane.
3. The preparation process according to claim 1, characterized in that: In step two, the polyether polyol is polytetrahydrofuran ether diol with a number average molecular weight of 1800 to 2200, and the amount added is 100 parts by weight; the diisocyanate is 4,4'-diphenylmethane diisocyanate, and the amount added is 28 to 35 parts by weight; the heating temperature is 80°C to 85°C.
4. The preparation process according to claim 1, characterized in that: The cooling conditions described in step three are at a temperature of 5°C to 10°C; the chain extender is ethylenediamine, and the amount added is 0.8 to 1.5 parts by weight; the end-capping agent is diethylamine, and the amount added is 0.1 to 0.3 parts by weight; the predetermined viscosity is 180 Pa·s to 220 Pa·s measured at 40°C for the reaction system.
5. The preparation process according to claim 1, characterized in that: The hollow silica nanospheres in step one have an average particle size of 50 nm to 150 nm, a wall thickness of 5 nm to 15 nm, and a hollowness of over 40%.
6. A modified heat-insulating spandex fiber, characterized in that: The fiber is produced by dry spinning of a modified polyurethane spinning solution obtained by the preparation process described in any one of claims 1 to 5.
7. The modified heat-insulating spandex fiber as described in claim 6, characterized in that: The dry spinning process parameters include: a filtration accuracy of 20 μm for the spinning assembly, a spinning tunnel temperature of 180°C to 220°C, a winding speed of 500 m / min to 700 m / min, and a fiber fineness of 40 D to 70 D.
8. A knitted elastic composite sportswear set, characterized in that, The fabric of the sportswear includes the modified heat-insulating spandex fiber as described in claim 6.
9. The knitted elastic composite sportswear set as described in claim 8, characterized in that: The fabric of the sportswear set adopts a yarn-knitted structure, with the modified heat-insulating spandex fiber as the ground yarn and the moisture-wicking polyester filament or nylon filament as the face yarn; the feeding tension of the ground yarn during the knitting process is 5cN to 10cN.
10. The knitted elastic composite sportswear set as described in claim 9, characterized in that, The moisture-wicking polyester filament is an irregularly shaped cross-section fiber with a specification of 75D / 72F.
Citation Information
Patent Citations
Method for preparing micropore hollow polyurethane elastic fiber
CN109537093A
